Oxalate nephropathy in cattle associated with the consumption of Megathyrsus maximus in Argentina - Avellaneda Cáceres, Agustín; Lee, Stephen T.; Ruiz, Alvaro Francisco; Sandoval, Gabriela Virginia; Colque Caro, Luis Adrián; Cook, Daniel; Aguirre Castro, Laura Sabrina; Uzal, Francisco A.; Micheloud, Juan Francisco (Sage Publishing, 2025)
Over a 2-wk period, 20 cows that were grazing a Megathyrsus maximus (Guinea grass) pasture died after developing depression, respiratory difficulty, and recumbency. Affected animals had increased serum urea, phosphorus, and creatinine concentrations, and below-normal calcium concentrations. Autopsy revealed moderate ascites; mildly enlarged, pale, mottled kidneys; and perirenal edema. Microscopically, there was hyperplasia of mesangial cells in the renal glomeruli, renal tubular epithelial necrosis, and hyaline casts and refractive crystals in cortical and medullary renal tubular lumens. Samples of M. maximus from the affected pasture contained elevated concentrations of soluble oxalate (3.71%). Our findings suggest that oxalate produced by M. maximus caused acute tubular injury. Our case highlights the critical need for monitoring oxalate levels in pastures and managing grazing practices, particularly under drought conditions, to prevent similar outbreaks in the future.